Towards an Alternative Development Management Paradigm? - Shutt, Cathy (Expertgruppen för biståndsanalys (EBA), 2016)
Demonstrating results has been a concern in international development cooperation ever since it was started and in recent years there has be en an increased focus on achieving and reporting on “results”. Despite the fact that everyone involved in development cooperation wants to m ake a difference there has been a growing criticism from practitioners about the “results agenda” based on a concern that the approaches use d are not fit for purpose. In the EBA-report, Cathy Shutt, at the Univ ersity of Sussex, scrutinizes the recent critical debate about results based management, and the main arguments and motives behind the criti cism. She shows that the debate is not only a matter of obsessive meas urement and reporting of meaningless numbers for political accountabil ity, but also a matter of problematic assumptions and how we think abo ut development, evidence and learning. In the report, Shutt also explo res what could be learned from those who are not just critiquing resul ts based management approaches but also proposing alternatives. Are th ese new alternatives an answer to the criticism?
Keywords: IMPORTANT